"We're Not Going to Overcome Institutional Bias by Doing Nothing": Latinx/a/o Student Affairs Professionals as Advocates for Equity - Michelle M. Espino; Juanita Ariza (MDPI AG, 2022)
Higher education institutions continue to be contested environments where the goals of equity and inclusion are often at odds with the permanence of institutional racism. Through a multi-case study of 19 Latinx/a/o mid-level administrators who worked at 16 predominantly white, private four-year universities, the authors uncovered the ways that (a) private universities grant agency to Latinx/a/o mid-level administrators to serve student needs but restrict agency to address the inequitable organizational structures; (b) constituent groups within private universities, namely faculty, mark the racialized boundaries of power and decision-making through credentialing; and (c) private universities use silence as a means of controlling Latinx/a/o mid-level professionals administrators' equity work. Although Latinx/a/o mid-level administrators have a significant role to play in advancing equity work inside higher education institutions, these racialized organizations will create barriers that maintain whiteness and white interests. Without addressing power structures and the bureaucracy of decision-making at private institutions, progress on equity throughout the organizational structure may be limited. Implications for research and practice for Latinx/a/o/ administrators are discussed.